The structural modifications of Candida albicans cells after treatment with Cinnamomum zeylanicum blume crude extract / Noor Hazarina Nordin, Darah Ibrahim and Siti Nurdijati Baharuddin - Nordin, Noor Hazarina; Ibrahim, Darah; Baharuddin, Siti Nurdijati (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
The fungal species Candida albicans is an opportunistic pathogens which causes serious infections in humans, particularly in immunocompromised patients. Cinnamomum zeylanicum (cinnamon) or locally known as "kayu manis" has been reported to possess potent antifungal activity. Thus, this study evaluated the effects of C. zeylanicum chloroform extract on cell morphology ofC. albicans by observing the extract-treated yeast cells through scanning electron microscopy (SEM). Candida albicans cells morphology was observed to be lysed after 48 hours at various time intervals of exposure to the extract. The results indicated that the severity effect of cinnamon extract on the yeast cells was dependent on the time of exposure, and that the C. zeylanicum can inhibit filamentous growth of C. albicans cells. Electronic microscopy observations revealed that the sodium chloride (NaCl) crystals were probably primarily produced due to the extract-yeast reactions, which then contributing to the cells death. It is concluded that the cytoplasmic membrane is involved in the toxic action of the cinnamon crude extract.